2013
DOI: 10.1246/cl.130153
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis and Lateral π-Expansion of Bisanthenes

Abstract: The improved Scholl reaction allows for the direct cyclization of anthracene oligomers to give bisanthene, teranthene, and quateranthene. Furthermore, a variety of π-expanded bisanthenes are obtained by the Diels–Alder cycloaddition of bisanthene with several arynes. These reactions would allow us to synthesize various size- and shape-controlled polyperiacenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 43 publications
1
35
2
2
Order By: Relevance
“…Die hohe Ringspannung in diesen Makrocyclen verhinderte jedoch eine saubere und selektive Cyclodehydrierung zu CNT-Segmenten, und es wurden stattdessen unvollständig reagierte,c hlorierte oder 1,2-Phenyl-umgelagerte Verbindungen erhalten. [38] [39][40][41][42][43][44] In früheren Studien wurden für die nichtmethylierten [3]CHPBs 3 1,2-Phenylwanderungen beobachtet (Schema 2a). Da sich nun Alkylketten an diesen kritischen Positionen befinden, wurde,t rotz der immer noch hohen Ringspannung und der Verdrillung der Vorstufen 5a, b und 6,e ine selektive Synthese der Phenylen-erweiteten [3]CHBCs 7a, b und 8 erwartet.…”
unclassified
“…Die hohe Ringspannung in diesen Makrocyclen verhinderte jedoch eine saubere und selektive Cyclodehydrierung zu CNT-Segmenten, und es wurden stattdessen unvollständig reagierte,c hlorierte oder 1,2-Phenyl-umgelagerte Verbindungen erhalten. [38] [39][40][41][42][43][44] In früheren Studien wurden für die nichtmethylierten [3]CHPBs 3 1,2-Phenylwanderungen beobachtet (Schema 2a). Da sich nun Alkylketten an diesen kritischen Positionen befinden, wurde,t rotz der immer noch hohen Ringspannung und der Verdrillung der Vorstufen 5a, b und 6,e ine selektive Synthese der Phenylen-erweiteten [3]CHBCs 7a, b und 8 erwartet.…”
unclassified
“…[39][40][41][42][43][44] In previous studies a1 ,2-phenyl shift was observed for the nonmethylated [3]CHPBs 3 (Scheme 2a). [39][40][41][42][43][44] In previous studies a1 ,2-phenyl shift was observed for the nonmethylated [3]CHPBs 3 (Scheme 2a).…”
Section: Thesynthesisofmonodisperselength-mentioning
confidence: 81%
“…As af inal step to form graphenic sidewalls,t he macrocycles 5a, b and 6 were subjected to cyclodehydrogenation with iron chloride at room temperature (Scheme 2). [39][40][41][42][43][44] In previous studies a1 ,2-phenyl shift was observed for the nonmethylated [3]CHPBs 3 (Scheme 2a). Yetb yh aving alkyl chains at these critical positions,t he selective synthesis of phenylene extended cyclic hexa-peri-hexabenzocoronene trimers ([3]CHBCs) 7a, b and 8 is expected, even if the ring strain and distortion were still high for 5a, b and 6.…”
Section: Thesynthesisofmonodisperselength-mentioning
confidence: 81%
“…The 1 Ha nd 13 C{ 1 H} NMR resonances of all target compounds and intermediates were assigned and are fully consistent with the proposed molecular structures.T ypical for triarylboranes,t he 11 Thec yclic voltammogram (CV) of parent dibenzo-[g,p]chrysene in CH 2 Cl 2 shows several ill-defined features in the oxidizing region;n or eduction potentials have been reported. [18] In comparison, the planarized, doubly Si-bridged 11 (cf.T able 1) undergoes reversible oxidation at E 1/2 = 0.81 V (vs.FcH/FcH + ;CH 2 Cl 2 ); no reduction events are observed up to the limit of the solvents potential window at À2.3 V. The boron-bridged dibenzo [g,p]chrysenes show an increased redox activity:C ompound 9 gives rise to two reversible redox events at E 1/2 = 1.00 Vand À2.01 V, whereas the CV of 12 is characterized by three reversible one-electron transitions at E 1/2 = 1.09 V, À1.85 V, and À2.14 V. For7 ,14-di-(mesityl)bisanthene,t he all-carbon congener of 12, [19] halfwave potentials have been reported at 0.65 V, 0.02 V, and À1.66 V, together with apeak potential at À2.19 V, the latter indicating an irreversible electron transfer.T hus,wef ind the boron-containing compound 12,w hich is isoelectronic to the 7,14-di(mesityl)bisanthene dication, harder to oxidize by 1V than 7,14-di(mesityl)bisanthene itself.T he reduction potentials of both compounds,h owever, are rather similar ( Table 1). Each of the investigated type D compounds gives rise to one reduction wave between E 1/2 = À2.0 Vand À2.2 V. In addition, the methyl-substituted derivative 8a can be reversibly oxidized at ap otential value of E 1/2 = 0.99 V; the bipolar species 8d undergoes two redox transitions at E 1/2 = 0.94 Vand 0.48 V. TheCF 3 -and 2-thienyl-substituted species do not show interpretable oxidation waves.…”
Section: Methodsmentioning
confidence: 99%